Spatial heterogeneity of human activities and its driving factors in karst areas of Southwest China over the past 20 years - Chen, Chen; Xu, Yufeng (Frontiers in Environmental Science, 2023)
Guizhou Province is located in the karst mountain regions of Southwest China, where the ecological environment is extremely fragile and particularly sensitive to human activities. Therefore, understanding the changing characteristics and driving factors of human activity in recent decades is urgent. Based on a large collection of nightlight data, topography data, and meteorological data, combined with geographical information technology, we investigated the spatial distribution, intensity change, and degree of impact of human activity from 2000 to 2020. During the study period, human activities intensity and range were expanding. The human activity areas expanded from 15963 km 2 to 86923 km 2 with an increased rate of 4279.2 km 2 /a, which was 1118.4 km 2 /a from 2000 to 2010 and 6375.3 km 2 /a from 2010 to 2020. The human activity intensity was increased from 0.009 to 0.018 with an increase rate of 0.0006/a, which was 0.00028/a from 2000 to 2010 and 0.00073/a from 2010 to 2020. The rate of increase in the human activity intensity and the rate of expansion of human activity range during 2010-2020 was significantly higher than that during 2000-2010, and became more notable (p≤0.01), especially after 2012. With the expansion of human activities, the center of gravity of human activity moved towards the northeast direction by 20.71 km. The human activity intensity and level of urban development were high in the middle, southwest, and northeast of Guizhou. The human activities were primarily distributed in areas with gentlest slopes (6-15°), middle and low altitude (489-1,982 m), suitable temperature (12.36-17.74 ℃), and abundant precipitation (1,001.99-1,276.99 mm). The research results using the GeoDetector model indicate that slope has the greatest impact on human activities with q value of 0.1338, and precipitation, elevation and temperature with q value of 0.0626, 0.0253 and 0.0136 respectively. The combined impact between precipitation and slope was greatest with q value of 0.1803. In Guizhou Province, under policy guidance, human activities that promoted vegetation change accounted for 79.60%. This study attempts to enhance sustainable development and can provide valuable information for the environmental protection of karst mountain regions.